PENGARUHBUDAYALAYANANPRIMATERHADAP KEPUASANPELANGGANPUSKESMAS PANGKALAN KERINCI KABUPATEN PELALAWAN - Norman, Vera (Jurnal Ilmu Administrasi Negara, 2016)
In the decentralism era, the public service has been removing from government orientedto public satisfaction. This research is aimed to know the influence of primary services culturaltowards customer satisfaction At Puskesmas Pangkalan Kerinci Kabupaten Pelalawan. The samplesof this research are 87 patients by using accidental sampling technique. Data collecting throughquestioners with 5 option answers: very good ( 5), good ( 4) ,good enough (3), not good (2), bad ( 1 ).Data analisys for each variabele uses simple regresion analysis. This research result indicated thatthe influence of primary service culture shows a good category for customer satisfaction andsatisfied catergory for customer satisfactions. The influence of primary services culture towardscustomer satisfaction is significant, while is contribution to customer satisfaction is only 2, 7% and97,30% is influenced by other factors.